The Development of Fanzzle (Fauna Puzzle) Learning Media to Enhance Early Childhood Focus - Neuneu Nur Alam; Nita Priyanti; Chandra Apriyansyah (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
Focus is a fundamental cognitive ability that underlies successful learning in early childhood. This study aims to: (1) develop the FANZZLE learning media suitable for improving the focus of children aged 5–6 years; (2) examine the feasibility of the FANZZLE learning media based on expert validation; and (3) test the effectiveness of the media in enhancing children's focus. This research employed a Research and Development (R&D) method using the 4D development model (Define, Design, Develop, Disseminate). The research subjects consisted of 29 children aged 5–6 years at TKIT Ar’rosyiid, divided into two groups: B1 (14 children) and B2 (15 children). Research instruments included a needs analysis interview guide, expert validation sheets, and observation sheets measuring children’s focus through four indicators: engagement duration, engagement intensity, resistance to distraction, and attentional flexibility. Data were analyzed using qualitative descriptive analysis for needs assessment, feasibility percentage analysis for expert validation, and N-Gain analysis to measure effectiveness. The results showed that the FANZZLE media was categorized as “highly feasible” with an average validation score of 93.33%. The media also proved effective in improving children's focus, indicated by an increase in the mean score from 7.76 (pretest) to 12.62 (posttest) with an N-Gain score of 0.595 (moderate–high category). These findings indicate that FANZZLE learning media is both feasible and effective for improving the focus of children aged 5–6 years in early childhood education.